Survey and classification of some termites' species in some arid area (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
The survey results were illustrated that there were eight termites' species which were identified according to shape and structure of soldier head-capsule (namely, Anacanthotermes ochraceus, Heterotermes aethiopicus, Angulitermes arabiae,: Microtermes sp., Amitermes desertrum, Microcerotermes parvulus, Microcerotermes sp. found at arid area in Taif governorate, Saudia Arabia. The most common one was Anacanthotermes ochraceus which was recorded at all investigated area, except, El Hada (west Taif). In addition to three termites species were recorded to first time in Taif governorate, Saudia Arabia (namely, Microcerotermes parvulus, Heterotermes aethiopicus and Angulitermes arabiae).